Exploring the impact of disruption on university staff resilience using the dynamic interactive model of resilience (Journal of Applied Learning and Teaching, 2023)
The unanticipated changes in Higher Education settings brought about as a result of COVID–19 resulted in a range of personal, pedagogical and organisational challenges. This paper reports on research undertaken within a university in South West England, exploring how the pandemic impacted the working practices of academic and professional staff, the implications of those changes and the factors the respondents interpreted as influencing their resilience.A mixed methods approach was adopted whereby data were gathered from 159 academic and professional staff members using an online survey. Nine respondents were then individually interviewed. The data were analysed using the Dynamic Interactive Model of Resilience (DIMoR) in order to explore protective and risk factors from the various systems surrounding the respondents, alongside their more personal vulnerabilities/invulnerabilities.The results highlight the importance of considering individual and wider contexts when analysing the potential for resilience to emerge in times of disruption. The significance of movement of proximal and distal influences depending on the individual and their context also emerged, offering implications for university leaders to consider in supporting staff within their institutions. The value of the DIMoR is discussed as a lens for analysis to support understanding and future action.